Strategy for the inheritance of Penginang Penampi dance in Lombok Central West Nusa Tenggara - Baiq Larre Ginggit Sekar Wangi; Agus Cahyono; Deasylina Da Ary (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2022)
Penginang Penampi dance has become part of the culture of the people of Central Lombok. Shows are held only on official occasions. The existence of the Peninang Penampi dance, which is now being threatened by modern culture, needs to be saved. This study aims to discuss the inheritance of the Peninang Penampi dance in Central Lombok Regency, West Nusa Tenggara. This study used the descriptive qualitative method. Data collection methods to be used are interviews, observation and documentation. This qualitative research will look at art from several disciplines. The results of the study show that through the inheritance strategy of the Peninang Penampi Dance in Central Lombok Regency, West Nusa Tenggara, many aspects can also be saved and their existence maintained, including aspects of educational values, religious values, ethical values, aesthetic values and social values. The conclusion is that the inheritance strategy for the Peninang Penampi Dance is an inheritance process that continues to move dynamically; this is because socio-cultural changes continue to occur, so this research makes an important contribution in offering a concept of an approach to inheriting traditional dance based on local values of the people of Central Lombok Regency, West Nusa Tenggara.